Pengaruh Intensitas Penggunaan Tik Tok Terhadap Gratifikasi Penggunanya - Sri Wahyuning Astuti; Dyah Sri Subandiah (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2021)
AbstractThe TikTok application until April 2020 has increased its usage to reach 2 billion downloads. Indonesia is the country with the highest number of Tik Tok downloaders in the world. In a day 100 videos or about 39 minutes are used by Tik Tok users in Indonesia watching videos. This study aims to determine the motives for selecting media (uses and gratification) with the habits of Tik Tok users. Of the 6 motives that underlie media selection (uses and gratification), the results of the study reveal that most tik tok users in Indonesia have a motive to seek information and spend time. In addition, there was a positive relationship between the choice of the motive for using Tik Tok with user habits with a correlation value of p <0.005 and R = .662.Keywords : Tik Tok, Uses and Gratification, User HabitAbstraksiAplikasi TikTok hingga April 2020 mengalami peningkatan penggunaan hingga mencapai 2 Milyar unduhan. Indonesia menjadi negara dengan jumlah pengunduh Tik Tok terbanyak di dunia. Dalam sehari 100 video atau sekitar 39 menit digunakan oleh pengguna Tik Tok di Indonesia menyaksikan video. Penelitian ini bertujuan untuk mengetahui motif pemilihan media (uses and gratification) dengan kebiasaan pengguna Tik Tok. Dari 6 motif yang mendasari pemilihan media (uses and gratification), hasil penelitian mengungkap sebagian besar pengguna tik tok di Indonesia memiliki motif untuk mencari informasi, dan menghabiskan waktu. Selain itu didapatkan hubungan yang positif antara pemilihan motif penggunaan Tik Tok dengan kebiasaan pengguna dengan nilai korelasi p < 0,005 dan R= .662.Kata Kunci: Tik Tok, Uses and Gratification, Intensitas Penggunaan